Business strategy as human rights risk: the case of private equity - Birchall, David (Human rights review, 2023)
In this article, we apply the UN Guiding Principles on Business and Human Rights to the private equity (PE) business model. PE firms often adopt a controversial, ‘value extractive’, business model based on high debt and extreme cost-cutting to generate investor returns. PE firms own large numbers of companies, including in many rights-related sectors. The model is linked to increased human rights risks to workers, housing tenants, and in privatized health and social care. We map these risks and analyse the human rights responsibilities of PE firms. Our analysis has major implications for understandings of human rights responsibility. We argue that value extractive methods are the root cause of eventual harm to human rights, even though they may not harm rights directly. To respect human rights, PE firms must mitigate the risks of these value extractive methods. We define how human rights due diligence (HRDD) could achieve this and argue that given the extent of harm and the lack of a business case for adopting such a view of human rights responsibility, business strategy level HRDD should be a core component of forthcoming HRDD laws.